A National Modified Delphi Consensus Process to Prioritize Experiences and Interventions for Antipsychotic Medication Deprescribing Among Adult Patients With Critical Illness. (1st December 2022) - Jaworska, Natalia; Makuk, Kira; Krewulak, Karla D.; Niven, Daniel J.; Ismail, Zahinoor; Burry, Lisa D.; Mehta, Sangeeta; Fiest, Kirsten M.
Abstract : OBJECTIVES: Antipsychotic medications are frequently prescribed to critically ill patients leading to their continuation at transitions of care thereafter. The aim of this study was to generate evidence-informed consensus statements with key stakeholders on antipsychotic minimization and deprescribing for ICU patients. DESIGN: We completed three rounds of surveys in a National modified Delphi consensus process. During rounds 1 and 2, participants used a 9-point Likert scale (1—strongly disagree, 9—strongly agree) to rate perceptions related to antipsychotic prescribing (i.e., experiences regarding delivery of patient care), knowledge and frequency of antipsychotic use, knowledge surrounding antipsychotic guideline recommendations, and strategies (i.e., interventions addressing current antipsychotic prescribing practices) for antipsychotic minimization and deprescribing. Consensus was defined as a median score of 1–3 or 7–9. During round 3, participants ranked statements on antipsychotic minimization and deprescribing strategies that achieved consensus (median score 7–9) using a weighted ranking scale (0–100 points) to determine priority. SETTING: Online surveys distributed across Canada. SUBJECTS: Fifty-seven stakeholders (physicians, nurses, pharmacists) who work with ICU patients. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Participants prioritized six consensus statements on strategies for consideration when developing and implementing interventions to guide antipsychotic minimization and deprescribing. Statements focused on limiting antipsychotic prescribing to patients: 1) with hyperactive delirium, 2) at risk to themselves, their family, and/or staff due to agitation, and 3) whose care and treatment are being impacted due to agitation or delirium, and prioritizing 4) communication among staff about antipsychotic effectiveness, 5) direct and efficient communication tools on antipsychotic deprescribing at transitions of care, and 6) medication reconciliation at transitions of care. CONCLUSIONS: We engaged diverse stakeholders to generate evidence-informed consensus statements regarding antipsychotic prescribing perceptions and practices that can be used to implement interventions to promote antipsychotic minimization and deprescribing strategies for ICU patients with and following critical illness.